Comparative-Study of Fe-C Bead and Graphite Target Performance with the National-Ocean-Science-Ams (Nosams) Facility Recombinator Ion-Source - Klinedinst, D. B.; McNichol, A. P.; Currie, L. A.; Schneider, R. J.; Klouda, G. A.; vonReden, K. F.; Verkouteren, R. M.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
An accelerator mass spectrometry (AMS) experiment was designed to investigate C-14 target performance for two target types over a range of isotopic concentrations and sample sizes, with a special focus on the ability to measure C-14 in environmental samples having only microgram amounts of carbon. The findings were positive, showing that precision, accuracy, and stability were adequate to determine C-14 to 1% or better in samples containing as little as 25 mug carbon. Satisfactory Poisson uncertainty and target stability were demonstrated down to a level of 7 mug carbon, but experimental data showed that accurate measurements at that level require detailed knowledge of blank variability and mass dependence of the modern carbon calibration factor.
Nv547Times Cited:23Cited References Count:13